2014
DOI: 10.1016/j.neucom.2013.03.065
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive PID neural network for complex nonlinear system control

Abstract: Usually it is difficult to solve the control problem of a complex nonlinear system. In this paper, we present an effective control method based on adaptive PID neural network and particle swarm optimization (PSO) algorithm. PSO algorithm is introduced to initialize the neural network for improving the convergent speed and avoiding weights getting trapped into local optima. To adapt the initially uncertain and varying parameters in the control system, we introduce an improved gradient descent method to adjust t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 24 publications
0
57
0
Order By: Relevance
“…Numerous works [13][14][15] have demonstrated that ANN is suitable for dynamic and nonlinear control systems due to the capability of processing, analysing and learning. The speed controller of DTC structure is a nonlinear system, which hasdisturbances of load inertia and motor parametersvariation against temperature [12].…”
Section: Neural Network-pi Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous works [13][14][15] have demonstrated that ANN is suitable for dynamic and nonlinear control systems due to the capability of processing, analysing and learning. The speed controller of DTC structure is a nonlinear system, which hasdisturbances of load inertia and motor parametersvariation against temperature [12].…”
Section: Neural Network-pi Controllermentioning
confidence: 99%
“…For convenience of program coding work, the equation (8) can be described as incremental form as (9) [15]:…”
Section: Incremental Pi Controllermentioning
confidence: 99%
“…In light of the complexity and uncertainty of nonlinear systems, which widely exist in scientific and engineering fields, many efforts have been devoted to the solving of nonlinear system problems [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. As an important part of nonlinear system problems, the tracking control of nonlinear systems has attracted much attention in recent decades [6,7,9,10,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzy logic theory and neural network algorithm have been broadly researched to auto-tune the controller parameters on the basis of the prior rules [11][12][13][14]. However, large amounts of learning cost may be needed in these methods.…”
Section: Introductionmentioning
confidence: 99%